Valoración de inventario conforme a la norma internacional de contabilidad N°2 y NIIF en empresas dedicadas al comercio - Brito Castillo, Estefania del Carmen (2015)
This reason was based on the inventory of companies engaged in commercial activities whereas controlling is important for these companies in accordance with International Financial Reporting Standards Section N°13 for SMEs which indicates the procedures and records suitable for initial and final recognition. Regarding to this the Compañia Importadora Oro Auto INMOAUTO C. Ltda. Has not had adequate control and measurement of auto parts that which has made them avoid making decisions that affect profits. On this purpose it is proposed that auto-parts are carried at fair value in order to evaluate and update the value of assets based on the market. It is important to highlight that for this work scientific articles as a source of theoretical inquiry were used, in order to know the importance of proper control and inventory management in trading companies. The methodology used on this researching word were: interviews with company representatives who said they did not use a monitoring system to value items such as antenna, band distribution among others, has caused an inadequate control over it. Finally the purpose aims on improving and updating the record prices of auto parts that have low turnover of the company, this will be made based on the International Accounting Standard N°2 and IFRS that sets the method by inventories which are valued at fair in order to prevent the items are sold at historical value registered Kardex provides the accounting system and determine what the utility will get the end of the fiscal period.